Perceval S Sutureless Prosthesis in Aortic Valve Replacement - V. V. Sokolov; A. I. Kovalyov; V. V. Vladimirov; I. V. Ivanov; N. M. Bikbova (Неотложная медицинская помощь)
BACKGROUND In 12–47% of patients, there is a need to repeat the aortic valve replacement due to various valve-related complications in the immediate and late postoperative period. The standard operation of repeated aortic valve replacement is a complex procedure and it is associated with an increased risk due to adhesions in the pericardial cavity, previously performed coronary bybass surgery, diffculties of excision of the previously implanted prosthesis, narrow fbrous aortic valve ring and aorta. In 2007, the sutureless Perceval S aortic valve bioprosthesis (Sorin Group, Italy) was introduced into clinical practice. One of the advantages of such a prosthesis is the convenience of its anatomical positioning during repeated operations and the absence of the need to fx the prosthesis with sutures. The aim of study was to summarize the experience of sutureless implantation of the aortic valve prosthesis during repeated replacement.MATERIAL AND METHODS We report the results of treatment in 3 patients with valve-associated complications, who underwent aortic valve repeated replacement with the Perceval S sutureless prosthesis.RESULTS There were no hospital mortality and paraprosthetic regurgitation in the repeated replacement of the aortic valve with the Perceval S sutureless prosthesis. Two patients required implantation of a permanent pacemaker due to the development of a complete atrioventricular block, which was not related to the model of the prosthesis used.CONCLUSION The use of aortic valve prosthesis in cardiac surgery, which does not require fxation with sutures, allows non-standard decisions to be made in the surgical treatment of patients with various complications of previously performed aortic valve replacement and provides good immediate results if repeated replacement is necessary.